LEARNING EFFECT GUIDED INQUIRY MASTERY OF CONCEPTS ON BASIC MATERIALS COLLOIDAL SYSTEMS - Army Ardhi Andini; Ratu Betta Rudibyani; Emmawaty Sofya (Universitas Lampung, 2012)
The success of the learning process can be determined from the cognitive and affective aspects. One method involves learning activity of students to discover the concept itself is a method of guided inquiry (guided inquiry). One concept that requires the involvement of students in activities and make students more active is Colloidal Systems. The concept of colloidal systems require reasoning and explanations through reasoning. With such reasoning students can solve the problems and to apply them in everyday life. This study aimed to describe the effect of guided inquiry learning to mastery of concepts in the subject matter of the colloidal system. This type of research is experimental. The population in this study were all students of class XI Science SMAN 7 Bandar Lampung. Research sample class XI IPA 1 and XI IPA 2 selected using purposive sampling technique. The study design used was The Matching-Only Posttest-Only Control Group Design. Based on hypothesis testing, found that the average value of the colloidal system concept mastery class guided inquiry learning model applied is higher than the applicable class of conventional learning models. This shows that the application of the guided inquiry pembelajara affect colloidal systems concept mastery. Keywords: Effects, Guided Inquiry, Concept Mastery, Colloid Systems